Defining the mathematical dependencies of NOx and CO emission generation after biomass combustion in low-power boiler - Lukáč, Ladislav; Kizek, Ján; Jablonský, Gustáv; Karakash, Yevgeniy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper deals with the study of the influence of various factors, which have an impact on emissions such as NOx, CO, which have been verified by measurements. Biomass in the form of wood chips as fuel of different moisture content from 9% to 25% has been tested at various boiler outputs.
Keywords: wood chips; biomass combustion; emissions CO; emission NOx; wood chips moisture content; mathematical dependence of emission; low power boiler; zrębki drzewne; spalanie biomasy; emisja CO; emisja NOx; wilgotność zrębków drzewnych; matematyczna zależność emisji; kocioł małej mocy